Pengaruh Penyaluran Dana ZIS dan Pertumbuhan Ekonomi Terhadap Tingkat Kemiskinan di Provinsi Bengkulu Periode 2021-2024 - Agam Setiawan; Asnaini; Yenti Sumarni (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the impact of ZIS fund distribution and economic growth on poverty levels in Bengkulu Province during the 2021–2024 period. A quantitative research approach utilizing multiple linear regression analysis was employed. The study utilized secondary data, specifically ZIS fund distribution figures from the National Zakat Agency (BAZNAS) of Bengkulu Province and economic growth data from Statistics Indonesia (BPS) of Bengkulu Province, covering the 2021–2024 period on a monthly basis. The results indicate that ZIS fund distribution (X1) has a significant negative effect on poverty levels in Bengkulu Province, whereas economic growth (X2) does not have a significant effect; however, ZIS fund distribution and economic growth, when considered together, have a significant impact on poverty levels in Bengkulu Province during the 2021–2024 period.